A Method of Documentary Photography and its Application in a Student Project of Acculturation in Bali - Kuntjara, Aristarchus Pranayama (Nirmana, 2009)
I have devised a methodical research outline for students’ final projects that involve photography as their main medium. The method accommodates the two major kinds of photographic project characteristics. The first is the conceptual or the commercial type, and second is the observational or the photo story type. This article focuses on a photo story type project by a student who has followed the method closely. Osel Gunarso focused his study on documenting a unique acculturation between Christian tradition and Balinese customs in the village of Blimbingsari in Jembrana County, Bali. Through ethnography and qualitative analysis, Gunarso achieved visual discourse for understanding a cultural phenomenon. Although he had beautifully exhibited his documentary project, it also projected several problems and issues that would be important to consider in future projects with similar conditions, especially undergraduate final projects that are confined to a single semester. Technical and non-technical issues in documentary photography become significant and therefore must be addressed in advance along with the methodology.